2022
DOI: 10.1038/s41467-022-32963-0
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction promoted by m6A reader YTHDF3 through translation upregulation of FOXO3 mRNA

Abstract: Autophagy is crucial for maintaining cellular energy homeostasis and for cells to adapt to nutrient deficiency, and nutrient sensors regulating autophagy have been reported previously. However, the role of eiptranscriptomic modifications such as m6A in the regulation of starvation-induced autophagy is unclear. Here, we show that the m6A reader YTHDF3 is essential for autophagy induction. m6A modification is up-regulated to promote autophagosome formation and lysosomal degradation upon nutrient deficiency. METT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 109 publications
0
28
0
Order By: Relevance
“…In carcinogenesis studies, eIF3a has been recognized as a proto-oncogene, and may be a potential anticancer drug target in the eIF family ( 24 ). Recently, researchers found that eIF3a could involve in fibrosis through regulation of the TGF-β1 signaling pathway ( 27 ); the m 6 A reader YTHDF3 could recruit eIF3a to facilitate FOXO3 translation, subsequently initiating autophagy ( 28 ). These findings may provide directions for subsequent studies of eIF3a in the mechanisms of iNOA.…”
Section: Discussionmentioning
confidence: 99%
“…In carcinogenesis studies, eIF3a has been recognized as a proto-oncogene, and may be a potential anticancer drug target in the eIF family ( 24 ). Recently, researchers found that eIF3a could involve in fibrosis through regulation of the TGF-β1 signaling pathway ( 27 ); the m 6 A reader YTHDF3 could recruit eIF3a to facilitate FOXO3 translation, subsequently initiating autophagy ( 28 ). These findings may provide directions for subsequent studies of eIF3a in the mechanisms of iNOA.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated m6A modifications induced by METTL3 enable YTHDF3 to promote autophagosome formation and lysosomal function upon nutrient deficiency [ 153 ]. YTHDF3 binding to the m6A modifications at the coding DNA sequence (CDS) and 3′ UTR around the stop codon of Foxo3 mRNA facilitated FOXO3 translation and induced autophagy [ 155 ]. Enterovirus-71 (EV-71) infection induced autophagy [ 156 ].…”
Section: The Regulatory Roles Of M6a Writers In Autophagymentioning
confidence: 99%
“…Their results showed that YTHDF3 promotes autophagy by recognizing the modification of m 6 A sites near the stop codon of FOXO3 mRNA. YTHDF3 also recruits eIF3a and eIF4B to facilitate FOXO3 translation, which subsequently initiates autophagy [81]. Liang et al [82] reported that the decrease in m 6 A reader YTHDC1 inhibited autophagy by accelerating sequestosome1 (SQSTM1) nuclear mRNA decay in the keratinocytes of diabetic skin, resulting in impaired migration of keratinocytes and delayed wound healing.…”
Section: Ythdf and Ythdc Familymentioning
confidence: 99%